Pure yolk sac tumor of testis with lung metastasis in an adult patient - case report - Behera, Pushpanjali; Ahuja, Arvind; Bhardwaj, Minakshi (Medicine and Pharmacy Reports, 2020)
Pure yolk sac tumor is the most frequently seen testicular tumor in childhood; however it is usually a component of mixed germ cell tumor in adults. Pure yolk sac tumors are quite rare in adults. Pure yolk sac tumor in adults has been categorized as yolk sac tumor, post-pubertal type. We report a case of pure yolk sac tumor of right testis with lung metastasis in a 37-year-old man who was successfully treated by high inguinal orchidectomy and BEP combination chemotherapy.